Selective deletion of long but not short Cypher isoforms leads to late-onset dilated cardiomyopathy - Cheng, Hongqiang (Oxford University Press, 2011)
Cypher long (CypherL) and short (CypherS) isoforms are distinguished from each other by the presence and absence of three C-terminal LIM domains, respectively. Cypher isoforms are developmentally regulated, and mutations affecting both long and short isoforms are linked to muscle disease in humans. Given these data, we hypothesized that various Cypher isoforms play overlapping and unique roles in striated muscle. To determine the specific role of Cypher isoforms in striated muscle, we generated two mouse lines in which either CypherS or CypherL isoforms were specifically deleted. Mice specifically, deficient in CypherS isoforms had no detectable muscle phenotype. In contrast, selective loss of CypherL isoforms resulted in partial neonatal lethality. Surviving mutants exhibited growth retardation and late-onset dilated cardiomyopathy, which was associated with cardiac fibrosis and calcification, leading to premature adult mortality. At a young age, preceding development of cardiomyopathy, hearts from these mutants exhibited defects in both Z-line ultrastructure and specific aberrations in calcineurin–NFAT and protein kinase C pathways. Earlier onset of cardiac dilation relative to control wild-type mice was observed in young CypherL isoform knockout mice consequent to pressure overload, suggesting a greater susceptibility to the disease. In summary, we have identified unique roles for CypherL isoforms in maintaining Z-line ultrastructure and signaling that are distinct from the roles of CypherS isoforms, while highlighting the contribution of mutations in the long isoforms to the development of dilated cardiomyopathy.